Pengembangan Bahan Ajar Materi Debat Dengan Metode Role Playing Pada Siswa Kelas X Sekolah Menengah Atas - Ranem; Widyatmike Gede Mulawarman; Endang Dwi Sulistyowati (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2018)
The research materials development begins from the procurement process of the learning materials that are always revised with an uncertain time, contains a theme that is not necessarily in accordance with the problems that exist in the unit of education. The research is also conducted for positive character reinforcement because arguing activities often lead to selfishness in an effort to defend opinion, so debate participants often do not control the ethics of speech when arguing. Development research at class x students of SMA YPM Diponegoro Tenggarong Seberang used R&D technique approve and method while the learning system is reinforced Dick & Carey model. In collecting techniques are done by language validation techniques experts, tests, leaner’ responses, teacher’s responses, and interviews. The result showed that 20 out of 25 students (80%) completed the assessment of knowledge. Based on the observation of all teams capable of performing their duties well. The use of this method also makes the students able to achieve learning goals up to 96%. Based on the result of discussions with various parties, the role playing method is generally feasible to be used in the learning process and able to strengthen the character of leaners.